Thematic Roles in the Tale of "Macbeth" by E.F. Dodd - Doni Efrizah (Jurnal Humaniora Teknologi, 2019)
The research deals with predicates and arguments in the theoretical framework of Transformational Generative Grammar in terms of Thematic Roles or Theta Roles proposed by Chomsky (1981), Haegeman (1994) and his followers Radford (1981) and Ouhalla (1999). Thematic Roles may be defined as the participants of the arguments of a clause. It means that Thematic roles refer to the relationship between verbs and their arguments. Thematic Roles is focused to eight types of theta role. They are agent, patient, theme, experiencer, beneficiary/ benefactive, goal, Source and location. The analysis of Thematic Roles is taken form tne tale of â€œMacbethâ€ by E.F, Dodd in six tales of Shakespear. The result shows that agent is the biggest thematic roles found in the tale of Macbeth and source is the lowest one. Keywords: Thematic Roles, Verbs, Arguments